Corporate average fuel economy standards and the market for new vehicles - Thomas Klier; Joshua Linn (Federal Reserve Bank of Chicago, 2011)
This paper presents an overview of the economics literature on the effect of Corporate Average Fuel Economy (CAFE) standards on the new vehicle market. Since 1978, CAFE has imposed fuel economy standards for cars and light trucks sold in the U.S. market. This paper reviews the history of the standards, followed by a discussion of the major upcoming changes in implementation and stringency. It describes strategies that firms can use to meet the standards and reviews the CAFE literature as it applies to the new vehicle market. The paper concludes by highlighting areas for future research in light of the upcoming changes to CAFE.
Keywords: 330; CAFE; costs; structural estimation